PENGARUH GAYA HIDUP DAN ORIENTASI PASAR TERHADAP KEPUTUSAN PEMBELIAN PROPERTI DI PT. RIZKI MANDIRI - aditya Pratama; ahmad yudhira (VALUE, 2022)
The outbreak of the Covid 19 Virus that hit various parts of the world, made the development of property growth in various countries experience a drastic decline, including PT. Rizki Mandiri who was affected by the deadly epidemic. Housing that is comfortable and safe from various disturbances is highly preferred by consumers as a good place to live. Supporting facilities in residential locations are also an added value of the products to be sold. PT. Rizki Mandiri in this case, a company engaged in the property sector, provides attractive offers in selling its products, including designs that are different from other housing, strategic locations, public facilities around the housing location and excellent service in provide convenience in transactions. The purpose of this study was to determine the effect of lifestyle and market orientation on property purchase decisions at PT. Independent Rizki. The problem that occurs in this study is the selling price sold by PT. Rizki Mandiri has not been reached by all people, the types of houses offered are still not fully in accordance with consumer demand and some employees are still unable to provide explanations to consumers about the processes that consumers will go through in making Public Housing Credit (KPR), thus influencing consumer decisions. to buy housing products. The analysis used is associative analysis, this research method is quantitative. The population in this study were all consumers who bought a house at PT. Independent Rizki. The number of population and samples in this study amounted to 69 consumers. The results obtained from this study indicate that: 1) Lifestyle partially and significantly influences Purchase Decisions, 2) Market Orientation partially and significantly influences Purchase Decisions 3) Lifestyle and Market Orientation simultaneously and significantly influences Purchase Decisions . The results of the T-test scores processed with SPSS Version 20 were 9.473 > 1.66, 0 < 0.05 and 3.608 > 1.66, 0.001 < 0.05. The results of the F test produce Fcount 158,024 > Ftable 2.75 (n-k-1 at k = 69-3-1 = 65 at 3) so that Ha is accepted and Ho is rejected, meaning that Lifestyle and Market Orientation affect consumer satisfaction.